MANAGEMENT OF A PATIENT WITH SEVERE COURSE OF PSORIATIC ARTHRITIS - E. I. Alexeeva; T. M. Bzarova; A. N. Fetisova; S. I. Valieva; T. V. Sleptsova; K. B. Isaeva; R. V. Denisova; E. V. Mitenko; E.G. Chistyakova (Вопросы современной педиатрии)
A history case of a patient with psoriatic arthritis, characterized by severe disease course, systemic symptoms, significantly increased laboratory markers, polyarticular syndrome, typical skin and nails changes, rapid development of patient’s disability and low quality of his and his family life is presented in this article. The authors showed high efficacy of treatment with biological agent — etanercept. In 3 months of treatment non-active stage of disease was achieved, in 9 months — clinical and laboratory remission, not only of the articular syndrome, but also of the extra-articular and dermatological manifestations and laboratory markers of the activity.